Modeling maize price volatility in the East African market - Wambua, J.M.; Massawe, Stella C.; Wanjiku, J.; Guthiga, Paul M.; Ogada, M.; Karugia, Joseph T. (International Livestock Research Institute, 2011)
The global food system has become more susceptible to periods of extreme price volatility that impact on food security especially among the vulnerable groups. Highly volatile food prices subject market players to difﬁculties in planning ahead and adjusting to ﬂuctuating market signals. This paper investigates maize prices volatility in two East African (EA) countries; Kenya and Tanzania. The exponential GARCH model was used on monthly maize price data for the period 2003 to 2010, obtained from national institutions of the countries. The ﬁndings show strong evidence that in both markets; price volatility is not prone to new market information (good or bad news) but sensitive to market events. Further, price volatility was found to be greater and more persistent in Kenya than in Tanzania throughout the period under investigation. Interestingly, price volatility in Kenya reduced signiﬁcantly after 2005 when the country withdrew the import tariff on maize from other EAC member countries. The ﬁndings of this study show that prices of staples can be stabilized through increased cross border trade.